FEATURES OF MODERN YOUTH POLICY OF AZERBAIJAN IN THE LIGHT OF MODERN INTERNATIONAL TRENDS - Gabibova, Z.Z; Abdullaeva, M.R (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
Youth is the main driving force of society, the key to its development. The introduction of innovations in various spheres of public life is primarily associated with the activities of the young generation. In general, various projects and programs are being developed aimed at enhancing the role of youth in all spheres of public life; global partnerships are being established to implement meaningful action plans. The study of youth policy in individual countries is a prerequisite for the development of this field and achieves successful results. From history it is clear that youth policy went through a long evolutionary process, and only in the middle of the twentieth century was it formed as a concept. Ripening conditions and realities of life at the beginning of the last century gave rise to a new concept called "Enhancing the Role of Youth in Management". As a result, one of the key areas of United Nations development has been to harness the potential of youth at the international level. The creation of a mechanism for young ambassadors and the development of a UN youth strategy for 2014-2017 are part of this policy. The use of youth in society to achieve the goals of sustainable development is especially important in achieving effective and progressive results.